INVESTOR ASING DAN RETURN PASAR: APAKAH INVESTOR ASING MENDESTABILIZE BURSA EFEK INDONESIA - Ni Ketut Surasni; I Dewa Gede Bisma; hermanto hermanto; H Burhanudin; Iwan Kusuma Negara (Master of Management, Mataram University, 2019)
The purpose of this study is to analyze the impact of the presence of foreign investors on market returns on the Indonesia Stock Exchange. To see the impact of foreign investor trading activities, this study proposes three hypotheses that will be proven. The first hypothesis is that foreign investors will increase portfolio diversification or the so-called base-broadening hypothesis. The second hypothesis is that foreign investors will cause price pressures on stocks or the price pressure hypothesis. The third hypothesis is that foreign investors use certain strategies in their trading, namely the feedback trading strategy. Of the 401 companies selected 32 companies as samples. Furthermore, from the three hypotheses proposed, the only proven hypothesis is the price pressure. Thus, foreign investors can cause destabilize prices on the Indonesia Stock Exchange. The destabilize implication is that investors are possible to use negative feedback trading strategies to make a profit. Keywords: base-broadening, price pressure, feedback trading